Nonformal Education and Merdeka Curriculum Policy: The Leaders’ Perspective - Suryawahyuni Latief; Samsuddin; Ahmad Subhan (Studies in Learning and Teaching, 2024)
This study investigates the perspective of non-formal education leaders in Jambi province, Indonesia on the implementation of Merdeka curriculum policies in non-formal education providing equal education service managed by the community. Six leaders were selected using purposive sampling and data was collected through open-ended telephone interviews and one-on-one meetings. The findings revealed that the leaders had interesting experiences implementing the new curriculum, with a focus on providing non-formal education units. However, there were challenges in translating the curriculum structures into the operational curriculum of educational units, especially for students who are not of school age. The leaders suggested socialization, assistance, and training actively pour the curriculum into the operational curriculum. They also recommended support from the government in the form of material and non-material support. Further research is needed to evaluate the effectiveness of the policies and strategies used by non-formal education units in the implementation of the new curriculum, including those managed by the government and community, and to compare the implementation in non-formal and formal education units.